Antibiotics Susceptibility Profile of Gram-Positive Bacteria from Primary Health Centers in Jega, Kebbi State - Bilyaminu Garba Jega; Isa Musa Maishanu; Basiru Aliyu; Mohammed Ndagi Kasim (Borneo Journal of Pharmacy, 2022)
Nosocomial or healthcare-associated infection (HCAI) is an infection acquired during receiving health care that was not present during admission. The research aimed to determine the antibiotic susceptibility pattern of gram-positive bacteria isolated from Primary Health Centers in Jega Town. A total of fifty (50) swab samples were collected from 10 different health centers and analyzed using the streak plate technique. Pure bacterial isolates were maintained and characterized using biochemical tests; their percentage of occurrence show; Staphylococcus aureus 18 (43.9%), Enterococcus feacalis 8 (19.5%), Streptococcus spp 8 (19.5%), Bacillus cereus 4 (9.8%), and Staphylococcus epidermidis 3 (7.3%). McFarland standard solution was prepared and used to control inoculants, after which the antibiotic susceptibility pattern of the isolates was determined using the disc diffusion method. Staphylococcus epidermidis was resistant to Gentamycin, and other isolates were multi-drug resistant. In light of this research, there is a need for thorough disinfection and conscientious contact control procedures to minimize the spread of these pathogens in health centers where interaction between patients, HCWs, and caregivers is widespread and frequent.